Study on the effects of wave-induced setup on coastal evolution of the Cua Dai beach, Hoi An - Nguyen, Ngoc The; Tran, Thanh Tung; Nguyen, Trung Viet (Vietnam Journal of Marine Science and Technology, 2021)
Over the past years, there have been several studies on the hydrodynamic regime, beach erosion, and accretion at the Cua Dai beach in Hoi An city. However, there is still a lack of in-depth research on the effects of hydrodynamic factors on beach evolution in extreme weather conditions such as a storm event or during the Northeast monsoons, characterized by large waves mainly, especially. The wave set-up directly impacts on the evolution of upper beaches and coastal dunes, consequently causing beach erosion. This paper presents the results of nearshore wave propagation and transformation and the distribution of wave set-up during storms in the coastal area of Cua Dai, Hoi An, using the SWAN model and the XBEACH model. The models have been calibrated and validated using measured wave and water level data observed in the study area in October 2016. The simulation results have shown the overall picture of the influence of wave set-up on the morphology evolution of beach profiles in the study area.